CHARACTERISTICS OF ARTICLE TITLES IN HIGH-IMPACT LINGUISTICS & ENGLISH EDUCATION JOURNALS - Syaprizal Syaprizal; Safnil Arsyad; Wisma Yunita (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
The Title is an integral part of a journal article because it advertises the article to readers; if it is attractive, readers will read it. However, studies on the characteristics of article titles published in reputable journals in Applied Linguistics and English Language Education are scarce in the literature. Based on quartile rankings, this study compares the linguistic features and content structure of scientific article titles in reputable international journals in Applied Linguistics and English Language Education. Using a content analysis design, 982 article titles from 12 international journals published between 2022 and 2024 were analysed quantitatively and qualitatively. The results showed that the title length varied according to quartile: Q1 and Q3 had a higher average title length than Q2 and Q4, reflecting the tendency to use more descriptive titles in highly reputable journals. Linguistically, noun phrases were the most commonly used syntactic structure, but Q1 journals used compound constructions and -ing verb phrases that reflected the complexity and dynamics of ideas. Regarding content, the research method feature appeared most frequently, followed by data and findings, especially in Q1 and Q3 journals. In contrast, topic-only titles were more dominant in Q4 journals. These findings confirm that the structure of article titles reflects a scientific communication strategy tailored to the Journal's reputation. This study offers a conceptual contribution through a combined classification framework between linguistic features and title content. It provides practical guidance for academic authors in designing effective titles according to the expectations of target journals.